Evaluasi Managemen Nutrisi Pada Balita - Susi Wahyuning Asih (JURNAL KESEHATAN PRIMER, 2020)
Introduction: Complex nutrition is needed to support the growth and development of toddlers. Sufficient preparation must be done by the mother, as long as the toddler enters the process of growth and development so as to provide nutrition that is appropriate for the toddler during a period of growth and development. Nutrition Management for toddlers is very important. This study aims to find a picture of how nutrition management during the growth and development of toddlers, especially those carried out by mothers of toddlers. Method: this research uses a descriptive design with a survey approach. The population of all toddlers in RW 3, Dukuh Mencek, Sukorambi Jember sub-district was 43 mothers of toddlers with a large sample of 30 people. The study was conducted at posyandu in the village of Hamlet checking as many as 5 posyandu, data collection instruments using a questionnaire with a Likert scale. Results: this study was presented with a central tendency analysis in the form of the mean. Nutrition management for toddlers with a good category is 6 with a percentage of 20%, enough categories is 20 with a percentage of 66% while those with a less category are 4 people with a percentage of 14%. Conclusion: research shows that evaluation of nutrition management by toddlers by mothers is very important even though the results are in the quite dominant category. Evaluation of nutrition management in infancy by mothers contributes greatly to the toddler's growth and development stage. Increased knowledge in mothers of children under five and the application of nutrition management in Cathelya's community must be further promoted by health workers and cadres in charge. Pendahuluan: Nutrisi kompleks dibutuhkan untuk menunjang pertumbuhan dan perkembangan Balita, oleh karena itu Manajemen Nutrisi bagi balita ini sangatlah penting. Penelitian ini bertujuan untuk mengetahui gambaran bagaimana manajemen nutrisi pada masa pertumbuhan dan perkembangan Balita khususnya yang dilakukan oleh ibu balita. Metode: penelitian ini menggunakan desain deskriptif dengan pendekatan survey. Populasinya semua balita di RW 3 desa Dukuh Mencek kecamatan Sukorambi Jember sejumlah 43 ibu balita dengan besar sampel 30 orang. Penelitian dilakukan di posyandu yang ada di desa Dukuh mencek sebanyak 5 posyandu, instrumen pengumpulan data menggunakan kuesioner dengan skala likert. Hasil: penelitian ini disajikan dengan analisis tendensi sentral dalam bentuk mean. Manajemen nutrisi balita dengan kategori baik sejumlah 6 dengan pesentase 20%, kategori cukup sebanyak 20 dengan persentase 66 % sedangkan yang dengan kategori kurang sejumlah 4 orang persentasenya 14%. Kesimpulan: hasil penelitian menunjukkan bahwa evaluasi manajemen nutrisi balita oleh ibu sangat penting walaupun hasilnya dalam kategori cukup lebih mendominasi. Evaluasi manajemen nutrisi pada masa balita oleh ibu berkontribusi tinggi pada tahap tumbuh kembang balita. Peningkatan pengetahuan pada ibu balita dan aplikasi manajemen nutrisi diposyandu Cathelya harus lebih disosialisasikan lagi oleh tenaga kesehatan dan kader yang bertugas.